A Psychoanalysis Study of Pippa Midgley Character in Robert Galbraith's Novel The Silkworm - Agustinus Harry Pradata; Sistiadinita Sistiadinita (Faculty of Humanities, Diponegoro University, 2023)
This research aims to find out personality and describe the hierarchy of human needs in Pippa Midgley as a minor character in the novel The Silkworm (2018) by Robert Galbraith. This research is a qualitative content analysis because the data obtained in this study is descriptive data collected from a novel. For the data collection, the writer determined the type of data, took notes, and managed the data. The writer used the theory of the Big Five model by McCrae & Costa (1992) to find out the personality of Pippa Midgley. Further, the writer used the idea of the hierarchy of human needs by Maslow (1943) to describe Pippa Midgleyâ€™s needs. Before describing Pippa Midgleyâ€™s needs, the writer analyzed the personality traits of Pippa Midgley based on the category. This research showed that Pippa Midgley has a high personality of neuroticism, which consists of anxiety, vulnerability, and angry hostility. After that, the writer foundÂ out that the needs of Pippa Midgley follow the hierarchy of needs by Maslow which are psychology, safety, belongingness and love, esteem, and self-actualization needs. In addition, the high level of neuroticism in Pippa Midgley made her experienced obstacle in fulfilling the needs of self-actualization. This was because Pippa Midgley's neuroticism personality made her vulnerable, so she could not appreciate her potential.